Prognostic impact of local radiotherapy on metastatic urothelial carcinoma patients receiving systemic chemotherapy. (28th October 2019) - Abe, Takashige; Minami, Keita; Harabayashi, Toru; Sazawa, Ataru; Chiba, Hiroki; Kikuchi, Hiroshi; Miyata, Haruka; Frumido, Jun; Matsumoto, Ryuji; Osawa, Takahiro; Junji, Ishizaki; Tango, Mochizuki; et al.
Abstract: Objective: To clarify the prognostic impact of local radiotherapy on metastatic urothelial carcinoma patients treated by systemic chemotherapy. Methods: Of the 228 metastatic urothelial carcinoma patients treated with systemic chemotherapy, 97 received radiotherapy mainly to metastatic sites. In patients for whom the purpose of radiotherapy was not specified, more than 50 Gy irradiation was considered to be for disease consolidation for survival analysis, while less than 50 Gy was categorized as palliation. According to the Kaplan–Meier method, we analysed overall survival from the initiation of treatment for metastatic urothelial carcinoma until death or the last follow-up, using the log-rank test to assess the significance of differences. The Cox model was applied for prognostic factor analysis. Results: Overall, there was no significant difference in survival between patients with and those without radiotherapy ( P = 0.1532). When analysing the patients undergoing consolidative radiotherapy separately, these 25 patients showed significantly longer survival than the 72 patients with palliative radiotherapy ( P = 0.0047), with a 3-year overall survival of 43.3%. Of the present cohort, 22 underwent metastasectomy for disease consolidation, and there was no overlapping case between the metastasectomy cohort and cohort receiving consolidative radiotherapy. After controlling for four independent prognostic factors (sex, performance status, haemoglobin level and number of organs with metastasis) in our previous study, radiotherapy for disease consolidation showed a marginal value (hazard ratio = 0.666, P = 0.0966), while metastasectomy remained significant (hazard ratio = 0.358, P = 0.0006). Conclusions: In the selected patients, long-term disease control could be achieved after consolidative radiotherapy for metastatic urothelial carcinoma disease. Our observations suggest that local ablative therapy (surgery or radiotherapy) could facilitate long-term disease control. However, the treatment decision should be individualized because of the lack of randomized control trials. Abstract : In the selected patients, long-term disease control could be achieved after consolidative radiotherapy for metastatic urothelial carcinoma disease. Our observations suggest that local ablative therapy could facilitate long-term disease control.